Assessment of Responsibilities of Universities through Quality Assurance Information Published - Vu Anh, Bui; Hang, Nguyen Thi (VNU Journal of Science: Education Research; Vol 39 No 2DO - 10.25073/2588-1159/vnuer.4731, 2023)
Improving accountability in university autonomy is a trend of countries with advanced university governance in the world. The higher the degree of autonomy, the higher the transparency and accountability of activities in educational institutions is required. This brings sustainability to the autonomy mechanism, giving stakeholders confidence in the educational institution itself. To assess the quality of accountability of higher education institutions through this disclosure mechanism, the authors have studied the status of information disclosure of 107 Vietnamese higher education institutions. The evaluation is focused on the timeliness, completeness, transparency in publicizing the quality of education information. The research results show that there is a clear difference in public implementation, which is reflected in three main results, firstly, there is irregularity and incompleteness of the implementation of accountability, the number of non-implementation rate is quite high. Secondly, the disclosure of information is fully implemented by some groups of universities only. Thirdly, the results of One-Way ANOVA test on the mean difference between groups of universities showed that there was a difference with statistical significance p < 0.05. This demonstrates that there is a difference between the groups of universities studied in the implementation of accountability through the mechanism of quality assurance information disclosure.